IMAGE DAERAH TUJUAN WISATA: SUATU TINJAUAN DARI PERSPEKTIF WISATAWAN NUSANTARA - Martaleni Martaleni (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
Companies increasingly turn to the marketing based on the consumers’ image and emotions in order to win mind share and heart share. The management of a tourist destination image is an important factor in achieving success in business tourism. This study aimed to examine the effect of  service quality value towards the image, either directly or indirectly through tourist satisfaction as a moderating variable. Data obtained from the domestic tourists who visited tourist destination in Great Malang were analyzed by the method of Partial Least Square (PLS). The findings of this study explains that there are direct and indirect positive influence between the service quality value and the measurement of tourist object attraction, supporting means, empathy and feeling towards tourists’ image. Likewise there is a positive influence between satisfaction and tourist image.This study can help marketers (government agencies, private sectors in Great Malang), to better understand the contribution of the image of an increasing number of tourists. Thus marketers will be more careful in designing the right marketing strategy to make tourists  more loyal.